Analysis of Impact and Decision-Making Factors Affecting Alumni Working Outside Their Field of Study - Riski; Adam; Abdul Manab (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2025)
This study aims to analyze the impact and factors that influence the career decisions of alumni who work in fields unrelated to their majors, with a case study of alumni majoring in Islamic Guidance and Counseling (BKI) at the State Islamic University (UIN) Datokarama Palu. The phenomenon of mismatch between fields of study and the world of work is a major concern because it can have an impact on the psychological, social, and professional aspects of alumni. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with alumni who work outside the BKI field of study. The results show that alumni career decisions are influenced by internal factors such as changing personal interests and the need for self-actualization, as well as external factors such as limited job opportunities in their field of study, economic demands, and lack of career information. The impact of these decisions includes feelings of low self-confidence, social adjustment in new work environments, and limitations in developing professional skills in line with their fields of study.